Problematics of Learning the Qur'an and Hadith for Students of MAN 3 Kebumen - Nurhaliza, Putri Magda; Fauziah, Muna; Awanis, Atsmarina (Faculty of Education Universitas Nahdlatul Ulama Yogyakarta, 2026)
The purpose of this study is to analyze the problems of learning the Qur'an and Hadith in class XI B students at MAN 3 Kebumen. This study uses a qualitative research method with a case study approach with the object of research being the problems of learning the Qur'an and Hadith in class XI B MAN 3 Kebumen. The research subjects consisted ofan Al-Qur'an and Hadith teacher and 6 out of 31 class XI B students in the 2024/2025 academic year. The selection of the subjects was based on a purposive sampling technique. The criteria used included students who experienced problems in learning the Qur'an and Hadith with high, medium, and low categories. The data collected included observation, interviews, and documentation. The data were tested for validity using method and source triangulation. The data analysis techniques used included data condensation, data presentation, and drawing conclusions. The results of the study show that the problems of learning the Qur'an and Hadith were identified in the aspect of learning interest which was characterized by students having low learning interest, indiscipline in completing assignments, and playing with cellphones; the learning motivation aspect is characterized by students being less motivated, monotonous lecture methods, limited forms of appreciation given by teachers, and a non-conducive classroom environment; and the learning difficulty aspect is characterized by students having difficulty in mastering the material and showing a personality that does not support the learning process, such as drowsiness and sleeping.